Belanja Modal Memediasi Pengaruh Pendapatan Daerah Terhadap Pertumbuhan Ekonomi Daerah Otonomi Khusus - Utomo, Langgeng Prayitno; Asyik, Nur Fadjrih; Hermanto, Suwardi Bambang (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 2 (2017), 2017)
ABSTRACT The purpose of this study is to examine the effect of regional income on the economic growth of special autonomous regions mediated by capital expenditure. The sample of this study is the realization of regional income and expenditure budget of districts and municipalities in the special autonomous region of Papua province for the year of 2011-2015. By using purposive sampling technique, this study obtained 120 data observation report. The test is done by Structural Equation Modeling (SEM) technique. The test results indicate that the amount of regional revenue has a positive effect on economic growth, besides the regional revenue also has a positive effect on capital expenditure, then the addition of allocation amount on capital expenditure has a positive effect on economic growth. Capital expenditure is able to partially mediate the regional income on economic growth in the form of partial or partial mediation. Keywords: Capital expenditure, regional income, economic growth